THE EVALUATION OF SILICA+ SUPPLEMENTATION IN DIFFERENT TYPE OF DIET ON PERFORMANCE, NUTRIENT RETENTION AND THE ECONOMIC VALUE OF BROILERS DIET - Irfan Anshory; Sumiati Sumiati; Indah Wijayanti (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This study aimed to evaluate the effect of silica+ supplementation (Si) in different types of diet on performance, nutrient retention (energy, protein, fat), and the economic value of broiler diet. The treatment diets are 1. HN (high nutrient), 2. HN+Si, 3. LN (low nutrient), 4. LN+Si, 5. HNRB (high nutrient contained rice bran) and 6. HNRB+Si. A number of 1440 unsexed day old chicks (CP707 strains) were arranged in a completely randomized design consisted of 6 treatments and each treatment was replicated six times. The results showed that silica+ supplementation in HNRB and LN diets did not affect the performance and nutrient retention. The HNRB diet produced low fat retention, high FCR during starter period, and lower body weight during starter and grower period (P<0.05). The LN diet resulted high FCR during starter period (P<0.05), however it had no effects on the body weight. Silica+ supplementation on HN diet decreased the FCR by 8.09% during the grower period (P<0.05). Besides, it increased the fat retention and true metabolizable energy corrected by nitrogen (TMEn) by 1.30% and 4.41%, respectively. In general, silica+ supplementation was applied on the high nutrient diet during the grower period (22 to 35 days of ages) was effective. HN+Si produced the highest economic value diet in terms of income over feed and chick cost (IOFCC) increasing by 11.07% and relative feed cost (RFC) decreasing by 4.16%.